Performing citizenship illegally: The Nimis Groupe and political migrant theatre in Europe. (1st November 2019) - Paire, Roxane
AbstractThe Nimis Groupe are an international theatre collective made up of six Belgian and six French actors. Roxane Paire interviewed them in 2015 while they were working on a play entitled Ceux que j'ai rencontræ#169;s ne m'ont peut-être pas vu (Those that I've met probably did not see me). This piece focused on the legal mechanisms of asylum in the European Union and was performed by actors from the company who performed onstage alongside some of the migrants who had informed the research for the play. This intervention discusses the ethical implications of the European members of the company working alongside migrants who were not at that point legally recognized as citizens.